Комутативні області елементарних дільників та деякі властивості їх елементів - Щедрик, В.П. (Український математичний журнал, 2012)
Исследуются коммутативные области элементарных делителей с точки зрения изучения структуры обратимых матриц, которые приводят заданную матрицу к диагональному виду. Указаны некоторые свойства элементов таких областей. Установлены условия, близкие к условиям стабильного ранга, при которых коммутативная область Безу является областью элементарных делителей. We study commutative domains of elementary divisors from the viewpoint of investigation of the structure of invertible matrices that reduce a given matrix to the diagonal form. Some properties of elements of these domains are indicated. We establish conditions, close to the stable-range conditions, under which a commutative Bézout domain is a domain of elementary divisors.